Sifting through the Data : Labor Markets in Haiti through a Turbulent Decade (2001-2012) - Scot, Thiago; Rodella, Aude-Sophie (World Bank, Washington, DC, 2016)
In Latin America, labor markets have been the main channel through which growth has reduced poverty, with higher labor income accounting for 49 percent of the reduction in poverty in 2008–13. Understanding labor markets is critical to designing policies and programs aimed at reducing poverty. With close to 70 percent of the population under age 30 years, labor markets are bound to be central to defining Haiti's future. Yet, labor analysis in Haiti has been constrained by the dearth of data and the focus on measuring the impact of the 2010 earthquake. This present paper contributes to filling this gap by providing an overview of Haiti's labor markets and the determinants of labor income over a decade, focusing on growing urban areas. The paper also contributes to the research on Haiti in general, as well as labor markets in fragile countries such as Haiti, in particular through an unprecedented effort to harmonize three household surveys conducted between 2001 and 2012. Building on this exercise, the study provides new insights into the development of labor markets in a particularly turbulent decade for Haiti, one that was marked by the political crisis of 2004 and the earthquake of 2010. In spite of the earthquake, the analysis shows that Haiti’s labor markets are characterized by continuity over the period. Somewhat surprisingly, the defining features remain overall unchanged in spite of the shock, pointing to heavy forces shaping economic and labor dynamics.